Exploring The Interplay Of Organizational Commitment, Culture, And Job Satisfaction In Enhancing Employee Performance - Wuryanto, Wuryanto; Lahindah, Laura (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study investigates the relationships among organizational culture, organizational commitment, work-life balance, and job satisfaction in Bank XYZ, encompassing employees across various regional offices in/ Indonesia. Utilizing a quantitative research design, a survey was conducted with 304 respondents, including top management and staff. According to the findings, the culture of an organisation has a substantial impact on the level of commitment that employees have to their organisation, which in turn leads to increased job satisfaction. In addition, it has been determined that a healthy balance between work and personal life is a significant component that has a beneficial impact on both organisational commitment and job satisfaction. The results suggest that fostering a strong organizational culture and implementing effective work-life balance initiatives can lead to increased employee satisfaction and engagement, ultimately benefiting organizational performance. In addition to providing useful advice for enhancing employee outcomes, this research makes a significant contribution to the understanding of the significance of these components in the banking industry.